Interdiffusion of Zinc-Stannate Buffer Layer and Cadmium Sulfide Heterojunction and Its Correlation with CdCl2 Treatment - Ayad Khedhair Al-mebir, Alaa (University of Thi-Qar Journal of Science, 2019)
In this paper, a highly transparent and conductive Zinc Stannate (Zn2SnO4) buffer layer is integrated between the transparent conductive oxide (TCO) layer and the Cadmium Sulfide (CdS) window layer to improve the optical properties of (TCO\Zn2SnO4\CdS\CdTe) heterojunctions in CdTe\CdS solar cells. This buffer layer is used to reduce the excess interdiffusion between the window and absorber layers when Ultra-thin CdS window layer, d < 100 nm, is employed, and post CdCl2 treatment is applied at high temperature after deposition of CdTe layer. The fabricated Zinc Stannate (Zn2SnO4) buffer layer was found to have ideal transmission, reflectance and absorption properties which helped in introducing good optical properties in the short wavelengths. It has been found that using the Zn2SnO4 buffer layer enhanced the short circuit current Jsc and the open circuit voltage Voc of the solar cells that used Ultra-thin CdS thickness (80nm) by preventing TCO\CdTe direct contact, and led to improved solar cells’ performance and reproducibility.